2002
DOI: 10.1007/s004420100778
|View full text |Cite
|
Sign up to set email alerts
|

Testing the ecophysiological basis for the control of monoterpene concentrations in thinned and unthinned balsam fir stands across different drainage classes

Abstract: Stand thinning across different soil drainage types was used to test the ecophysiological basis for the control of foliar monoterpenes in current-year foliage of balsam trees [Abies balsamea (L.) P. Mill.] the year following treatment. Photosynthetic capacity (A ) was greater on mesic sites than on sub-hygric and hydric sites (1.81, 1.33 and 0.88 µmol m s, respectively) and greater in mid-July than at the end of June (1.86 vs 0.77 µmol m s). Foliar N was greater on thinned plots than control plots (2.6 vs 2.2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
0
5
0
1
Order By: Relevance
“…However, many factors can contribute to a lack of correlation between leaf N and A. The most likely are growth dilution of N with increasing LMA (Ellsworth and Reich, 1992;Castro-Díez et al, 2000), withinleaf allocation of N to other non-photosynthetic tissue (Abrams and Mostoller, 1995;Lamontagne et al, 2002), and the retranslocation of photosynthates and nutrients between current-year and 1-year old foliage (Maier and Teskey, 1992;Munson et al, 1995).…”
Section: Physiological Response and Acclimationmentioning
confidence: 99%
“…However, many factors can contribute to a lack of correlation between leaf N and A. The most likely are growth dilution of N with increasing LMA (Ellsworth and Reich, 1992;Castro-Díez et al, 2000), withinleaf allocation of N to other non-photosynthetic tissue (Abrams and Mostoller, 1995;Lamontagne et al, 2002), and the retranslocation of photosynthates and nutrients between current-year and 1-year old foliage (Maier and Teskey, 1992;Munson et al, 1995).…”
Section: Physiological Response and Acclimationmentioning
confidence: 99%
“…Needles of conifers contain secondary metabolites with defense functions ( Schonwitz et al, 1991 ; Carlow et al, 2006 ), of which monoterpenes are the dominant ones in resin ( Trowbridge et al, 2014 ). Their mechanisms of production are still poorly understood because several factors such as available nutrients ( Lamontagne et al, 2000 , 2002 ), water, C-reserve ( Trowbridge et al, 2014 ), and light ( Niinemets et al, 2004 ) influence their production. The concentration of monoterpenes can also be affected by the emission of volatile compounds ( Trowbridge et al, 2014 ) and their physicochemical characteristics such as volatility, solubility, and diffusivity ( Niinemets et al, 2004 ; Niinemets, 2010 ; Blanch et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have demonstrated that ecophysiological characteristics change in response to natural ranges of altitude, moisture, light gradients, and soil N availability (Kubiske and Abrams, 1992;Dudley, 1996;Muraoka et al, 1997;Jonas and Geber, 1999), as well as to gaseous air pollutants in controlled growth environments (Loats and Rebbeck, 1999). Recent ecosystem level studies have addressed the manner in which different treatments, such as prescribed burning and restoration thinning, affect fine-scale differences in leaf ecophysiological responses such as photosynthesis, nutrient concentration, and instantaneous nutrient use efficiency (Reich et al, 1990;Kruger and Reich, 1997;Fleck et al, 1998;Lamontagne et al, 2002;Wallin et al, 2004).…”
mentioning
confidence: 99%